Altitudinal Diversity of Dominant Vegetation Species in Relation to Soil Type in Himalayan Tract of Jammu - Rashid, Gulshan; Arora, Sanjay (Indian Forester, 2012)
The subtropical dry deciduous scrub and scattered cheer pine forests on the foothills of Siwaliks passes upward into the subtropical evergreen and sub-temperate vegetation of the hilly terrain of Siwaliks to the mixed deciduous and moist temperate and dry temperate forests of Sub-Himalaya and Pir panjal to the subalpine forest, alpine pastures and alpine scrubs of higher up Pir panjal range and higher Himalayas. Above the tree line, plant growth is limited by atmospheric cold, intense insolation and night time reradiation. Major contribution of the study include diverse species of plants in their specific geo-environment.